How Science Can Contribute to the Remedial Conservation of Cultural Heritage. Issue 42 (23rd June 2021) - Baglioni, Piero; Chelazzi, David
Abstract: Colloid science is contributing solutions to counteract the degradation of artifacts, favoring their transfer to future generations. Advanced materials such as nanoparticles, coatings, gels and microemulsions have been assessed in conservation, spanning from archeological sites to modern and contemporary art. We give an overview of the fundamental milestones and latest innovations in conservation science, targeting solutions and tools for remedial conservation based on green nanomaterials and hybrid systems. Future perspectives and outstanding challenges in this exciting field are then outlined. Abstract : Our society needs resilience to stand against social and environmental challenges. Cultural heritage assets are crucial as they foster socio‐economical improvements; however, they are threatened by degradation. We summarize here some of the most valuable solutions science has provided to systematically tackle degradation and re‐valorize our cultural patrimony, overcoming the serendipitous approach of past conservation practices.